Analisis Fatwa MUI Tahun 1982 tentang Mentasharufkan Dana Zakat untuk Kegiatan Produktif dan Kemaslahanatan Umum (Perspektif Yusuf Qardhawi) - M. Maulana Asegaf (Management of Zakat and Waqf Journal (MAZAWA), 2020)
This study seeks to answer an uproar issue some time ago in social media about the issue of allocating zakat funds for infrastructure purposes. Although, as reported in one of the electronic media, the head of the National Amil Zakat Agency (BAZNAS) has clarified that the issue is not true and may not be allocated for infrastructure but only for mustahiq. However, it is quite a shocking because already circulating in the social media, especially the existence of MUI fatwa seemed to legalize these activities in the name of fi sabillah. Therefore, the focus of this research is on the fatwa of the 1982 Indonesian Ulema Council about the allocation of zakat funds for productive interests and public benefit in the perspective of Yusuf Qardhawi. This research is library research using a descriptive qualitative method, in which the researcher observes the fatwa of MUI and various Islamic literature, especially on zakat. In order to find the light of the problem so that it can provide the best solution and not make muzakki feel worried about the zakat funds that they have given to Amil. The results of this research are: First, the allocation of zakat funds for infrastructure was not appropriate because there were still many Mustahiq who needed it more. Second, Zakat funds can be allocated if in an emergency such as if in a country education has been controlled by liberals, radicals, communists and atheists. Third, the allocation of zakat funds in the name of Fi Sabilillah must be in accordance with the agreement of Madzahib Arba’ah , which is only intended for people who are jihad in the path of Allah SWT. Fourth, According to Yusuf Qardhawi in the context of this era, jihad can use oral and written words, although it is not the same as jihad in the textual sense (war). However, by using qiyas, jihad (war) and jihad (non-war) can be equated with the same reason namely Nusrotul Islam.